Penerapan Pembukuan Sederhana Pada Usaha Warung Kelontong Di Desa Kalinongko Kabupaten Purworejo - Sefica Putri Adelia; Zaenal Wafa (Akuntansi, 2023)
A thriving economy based on the concept of populist economic development is largely derived from the MSME sector. The importance of insight into accounting greatly influences the success of running a business. However, many MSMEs in Indonesia do not apply accounting concepts in running their business. There are still many views that accounting does not need to be implemented among small entrepreneurs. Because of this, this research was conducted to determine the suitability of small entrepreneurs in applying the accounting concept carried out by the grocery shop entrepreneur Mrs. Paini in Kalinongko Village, Purworejo Regency. MSMEs in Indonesia play an important role in increasing the return on business and encouraging growth, strengthening the community's economy and expanding work networks. The grocery shop business is a type of MSME that has the potential to get profits quickly. This research is a field research that uses collection techniques through survey methods, socialization and direct training in the field. This activity begins with field observations, practices, and evaluations as well as reports. The results of this study indicate that the owner's knowledge of bookkeeping is still relatively low and many grocery shop owners do not understand the importance of applying accounting including bookkeeping and financial management so that many of them do not prepare financial reports but on the other hand they understand that bookkeeping is very important to implement. With this, they do not know the profit or loss they get.